Risk Factors of Acute Respiratory Infections in Children under Five Years Attending the Fishtail Hospital, Pokhara, Nepal - Koirala, R. (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Acute Respiratory Infection (ARI) is one of the leading causes of morbidity and mortality in under five-year children. Risk factors include age, sex, socio‐economic status, indoor air pollution, passive smoking, lack of basic health services, and lack of awareness. In this study, we aimed to determine the associated risk factors of ARI in children under five-years of age. Methods: We carried out a hospital-based descriptive cross-sectional study in the peak period of of November 2017 to February 2018. The study was conducted in Fishtail Hospital and Research Center (FHRC), Pokhara, Nepal. Non probability, purposive sampling technique was used and a structural interview was taken for data collection. The tool comprised of two main parts. Part I- questions related to socio-demographic variables of mother and baby. Part II- questions related to risk factors of ARI. The collected data was analyzed using Statistical Package for Social Science (SPSS) software, version 16. The Chi Square statistic is used for testing relationships between categorical variables. Results: In total of 302 children visited to FHRC with the symptoms of ARI, only 188 (63%) were diagnosed as ARI. The most common symptoms were fever (42.2%), cough (35.7%), running nose (34.1%), difficulty in breathing (28.5%) and chest in drawing (11.6%). The age of children with ARI ranged from one to sixty month with the mean age of 21.46 ±13.52. Among 188 children, 51% were males whereas 49%were females. There were no statistically differences of children weight at birth among ARI. Our results revealed environmental and social factors associated with ARI. Conclusions: The risk factors significantly associated with ARI were malnutrition, exposure to wood smoke and mosquito coil and contact with person having ARI. Reducing these conditions may reduce the morbidity and mortality associated with ARI in children.